2010
DOI: 10.1371/journal.pone.0010584
|View full text |Cite
|
Sign up to set email alerts
|

Patient Retention and Adherence to Antiretrovirals in a Large Antiretroviral Therapy Program in Nigeria: A Longitudinal Analysis for Risk Factors

Abstract: BackgroundSubstantial resources and patient commitment are required to successfully scale-up antiretroviral therapy (ART) and provide appropriate HIV management in resource-limited settings. We used pharmacy refill records to evaluate risk factors for loss to follow-up (LTFU) and non-adherence to ART in a large treatment cohort in Nigeria.Methods and FindingsWe reviewed clinic records of adult patients initiating ART between March 2005 and July 2006 at five health facilities. Patients were classified as LTFU i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
122
7
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(166 citation statements)
references
References 45 publications
32
122
7
1
Order By: Relevance
“…A South African study reported similar finding [39]. In addition, similar finding was reported in a multicenter study across Nigeria where female gender was reported to have lesser risk to loss to follow-up [40]. In this study, the odds ratio indicated that female respondents were 1.6 times more likely to be adherent, compared with males when multiple logistic regression of adherence to HAART with relevant predictors was conducted.…”
Section: Discussionsupporting
confidence: 85%
“…A South African study reported similar finding [39]. In addition, similar finding was reported in a multicenter study across Nigeria where female gender was reported to have lesser risk to loss to follow-up [40]. In this study, the odds ratio indicated that female respondents were 1.6 times more likely to be adherent, compared with males when multiple logistic regression of adherence to HAART with relevant predictors was conducted.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, 16% of the respondents believed that PLWHA had no hope. This belief could seriously hinder the ability of PLWHA to look into the future with a positive attitude and may affect their adherence to therapy, as positive Chi square test used attitude has been shown in several studies to contribute to good adherence to therapy [17,19].…”
Section: Discussionmentioning
confidence: 99%
“…Substantial rates of decline in the number of opportunistic infections and in the prevalence of AIDS-related mortality have been observed [12,13]. A number of studies have reported reductions in the level of plasma HIV-1 RNA and increases in the number of the CD4 cell count, even among PLWHA with very low initial CD4 counts [14][15][16][17][18]. Antiretroviral drugs must be taken as a lifelong therapy and their success relies on continual adherence to the medication regimen.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from two of three studies in the African setting that compared adherence in individuals initiating ART at high CD4 count with those initiating at lower CD4 counts were contradictory [5,6]. Furthermore, these two studies evaluated adherence in patients who were on an ART regimen based mainly on a thymidine analogue backbone (zidovudine or stavudine), known to be less tolerable than tenofovir-based regimens [7].…”
Section: Introductionmentioning
confidence: 99%